Case Report: Surgical management and prognostic factors in primary anorectal melanoma: a retrospective analysis of nine cases - Ren, Xiangxiang; Jin, Xiaoshi; Xie, Tianhao; Liu, Litao; Wang, Qiang; Sun, Xingli; Zhang, Meng (Frontiers in Medicine, 2025)
BackgroundPrimary Anorectal malignant melanoma (pARMM) is an exceedingly rare and aggressive malignancy, accounting for approximately 1% of anorectal cancers. It originates from melanocytes in the anorectal mucosa and lacks distinctive clinical features, leading to frequent misdiagnosis and advanced presentation.MethodsA retrospective analysis was conducted on 9 patients (1 male, 8 females; median age 59 years) with histopathologically and immunohistochemically confirmed ARMM who underwent surgical resection (Wide Local Excision, WLE = 4; Abdominoperineal Resection, APR = 5) and had complete follow-up data (median 19 months, up to May 2025). Diagnostic methods included clinical evaluation, digital rectal exam (DRE), colonoscopy, imaging (CT), histopathology, and immunohistochemistry (IHC). Treatment approaches and outcomes were analyzed.ResultsCommon presenting symptoms were hematochezia (44.4%), tenesmus (22.2%), altered bowel habits, anal mass protrusion, or were asymptomatic (11.1% each). DRE revealed exophytic (n = 6) or polypoid (n = 3) masses. Colonoscopy showed lesions near the dentate line; only 33.3% had obvious pigmentation. IHC positivity: HMB-45/Melan-A 66.7%, S-100 55.6%. Pathological R0 resection was achieved in all patients. During follow-up, 3 patients (33.3%) developed distant metastases (lung, liver), 2 of whom died. Six patients remained disease-free.ConclusionPrimary Anorectal malignant melanoma (pARMM) often presents with symptoms mimicking common benign anorectal conditions, leading to frequent diagnostic errors. Definitive diagnosis requires histopathological examination, with immunohistochemical markers (HMB-45 and Melan-A positivity) providing critical confirmation. While surgical resection remains the primary treatment, a growing expert consensus supports wide local excision with adequate margins (≥1 cm) as sufficient management. Emerging evidence indicates comparable survival outcomes to more radical procedures in appropriately selected patients.